The Role of Working Memory on Writing Processes - De Vita, Francesca; Schmidt, Susanna; Tinti, Carla; Re, Anna Maria (Frontiers in Psychology, 2021)
Literature has extensively demonstrated the coordination role of working memory (WM) in complex tasks such as writing. However, previous studies mostly concentrated on the relation between passive WM (e.g., WM span) components and specific writing tasks (e.g., dictation). Here, we aimed to investigate the relationship between different writing skills and the performance on a WM updating task measuring the more active components of WM. From a pool of 160 Italian pupils (grades 3–5), we selected 46 children divided in two groups based on their WM updating performance. The first group consisted of 21 children with low WM updating performance (≤10th percentile), the second group consisted of 25 children with high WM updating performance (≥90th percentile). All children were tested on a battery of writing tasks to assess writing speed, orthographic skills, and competences in expressive writing. MANOVAs and a discriminant analysis were computed to assess group differences and the contribution of the different writing tests in correctly predicting group membership. The results revealed that children with high WM updating performance scored significantly higher than children with low WM updating performance on most of the writing tasks. These results highlight the relevant role of the active components of WM on writing processes. In addition, they suggest that the improvement of writing skills should rely not only on the training of the specific processes implied in this complex task, but also on the training of the cognitive processes that support them, such as active WM processes.